The fungal microbiota modulate neonatal oxygen-induced lung injury - Isaac Martin; Mary Silverberg; Ahmed Abdelgawad; Kosuke Tanaka; Brian A. Halloran; Teodora Nicola; Erin D. Myers; Jay P. Desai; Catrina T. White; Ibrahim Karabayir; Oguz Akbilgic; Laura Tipton; et al. (Microbiome)
Abstract Background The immature lungs of very preterm infants are exposed to supraphysiologic oxygen, contributing to bronchopulmonary dysplasia (BPD), a chronic lung disease that is the most common morbidity of prematurity. While the microbiota significantly influences neonatal health, the relationship between the intestinal microbiome, particularly micro-eukaryotic members such as fungi and yeast, and lung injury severity in newborns remains unknown. Results Here, we show that the fungal microbiota modulates hyperoxia-induced lung injury severity in very low birth weight premature infants and preclinical pseudohumanized and altered fungal colonization mouse models. Instead of fungal communities dominated by Candida and Saccharomyces, the first stool microbiomes of infants who developed BPD had less interconnected community architectures with a greater diversity of rarer fungi. After using a pseudohumanized model to show that transfer to the neonatal microbiome from infants with BPD increased the severity of lung injury, we used gain and loss of function approaches to demonstrate that modulating the extent of initial neonatal fungal colonization affected the extent of BPD-like lung injury in mice. We also identified alterations in the murine intestinal microbiome and transcriptome associated with augmented lung injury. Conclusions These findings demonstrate that features of the initial intestinal fungal microbiome are associated with the later development of BPD in premature neonates and exert a microbiome-driven effect that is transferable and modifiable in murine models, which suggests both causality and a potential therapeutic strategy. Video Abstract